The first record of the giant pill-millipede genus Prionobelum Verhoeff, 1924 from Thailand, with the integrative description of two species (Diplopoda, Sphaerotheriida, Zephroniidae) - Donworth, Patrick; Wesener, Thomas (Zootaxa, 2024)
Thailand hosts a very rich but underexplored giant pill-millipede (Sphaerotheriida) fauna, with 11 of its 13 species described in the last three years. Currently, all known Thai giant pill-millipedes belong to the genera Zephronia Gray, 1832 (nine species) and Sphaerobelum Verhoeff, 1924 (four species). Here we describe the first two species of the genus Prionobelum Verhoeff, 1924 (previously restricted to Vietnam and China), Prionobelum inthanonense n. sp. and P. naevium n. sp. from Thailand. The species occur at Thailand’s highest mountain (2500 m) Doi Inthanon and the lowland rainforests at Bang Lang National Park touching the border with Malaysia. Both species are described integratively, utilizing light microscopy, scanning electron microscopy as well as DNA barcoding. Both new species of Prionobelum differ from other Zephroniidae species, as well as from one another, by more than 20% p-distance in the COI barcoding gene suggesting that potential closer related species are still awaiting discovery.